NEW MEDICAL INSTITUTIONS HAVE STARTED WORKING IN JARKURGAN (Proceedings of International Educators Conference, 2023)
In the Surkhandarya region of the Republic of Uzbekistan, 26 family polyclinics and 15 family medical centers have been launched in the past 2 years, and 15 this year, in order to make the primary medical service closer to the population.